(3NdGUI GdacQ aj TQM GdeNJUQ aj eUWdM Cgd GdCKQs - (3YHO Gddg GdTfThQjs; (3YHO Gddg Hf HgGA GdOjf GdTfThQjs
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ YHOGddg GdTfThQj aSCdfj LeGYI efge Cf CTQMgG dWjakG jhVMgG s
(3BNQgG (B:s
(3adJQGLY ai GdeHShWGJ cTQhM CdajI GdYQGbj hZjQgG ef GdeUfaGJ ajgG hZjQ Pdc hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ GdehUd (B(55) s
Keywords: (3GdMOjK h GdeUWdMs